PENGARUH PRAKTEK MANAJEMEN SUMBER DAYA MANUSIA TERHADAP BUDAYA ORGANISASAI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH PROVINSI KALIMANTAN TIMUR - Tri Astuti; Vera Anitra (Universitas Muhammadiyah Kalimantan Timur, 2019)
Human resource management is based on a concept that every employee is a human being, not a machine, and not merely a business resource. Human resources have a major role in every organization's activities, even though it is supported by facilities and infrastructures as well as excessive resources, but without the support of reliable human resources, the organization's activities will not be resolved properly. Human resource management has been widely practiced in everyday life, in reality management practices are not always easy and successful to influence people to work more productively. Globalization is increasingly inevitable and must be followed increasingly aware of Human Resources to pay more attention to national cultural factors, national culture and organizational culture. The purpose of this study is to examine the Influence of Human Resource Management Practices on Organizational Culture in the Regional Development Planning Board of East Kalimantan Province. Data is taken from a questionnaire distributed to 118 employees. The analysis technique used is Spss Multiple Linear Regression Analysis 22. The results of the analysis show that the practice of human resource management has a positive influence on organizational culture.